Learning a ranking function for information retrieval using HybridABC - Newaz, S.M Saif; Pieta, Maliha Anjum; Ahmed, Mehreen (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.